Effects of Stir Casting Baffles on Hardness and Microstructure: Investigation of Designed Aluminum Composites - Eko Surojo; Hammar Ilham Akbar; Dody Ariawan; Aditya Rio Prabowo; Teguh Triyono; Fahmi Imanullah (Civil Engineering Journal, 2022)
The increasing demand for lightweight material specifications has forced researchers to develop lightweight materials that are inexpensive, can be produced on a large scale, and are environmentally friendly. One solution that has been developed is an aluminum composite reinforced with sea sand. Indonesia has the second longest coastline in the world, which means that the country is rich in maritime resources, one of which is sea sand. The ceramic contents of SiO2, SiC, and Al2O3allow sea sand to be used as a reinforcement in aluminum composites for engineering purposes. The most effective manufacturing method of AA6061–sea sand composites is stir casting, but the homogeneity and distribution of particles are the main disadvantages of the stir casting method. Various factors affect particle distribution and homogeneity, one of which is the flow during the stirring process. The increase in turbulent flow in the stirring process affects the homogeneity and distribution of the particles. One way to create a turbulent flow when stirring is to add baffles. This paper examines the effect of adding baffles during the stir casting process on the mechanical properties of AA6061–sea sand composites. The mechanical properties of AA6061–sea sand composites were characterized using the Brinell hardness test according to ASTM E-10. The test results show that the addition of baffles during the stir casting process decreases the hardness of the AA6061–sea sand composites due to the turbulent flow that occurs. This makes the material more porous, which makes the AA6061–sea sand composites less hard. Doi: 10.28991/CEJ-2022-08-08-04 Full Text: PDF